Acute Promyelocytic Leukaemia with Differentiation Syndrome Treated Successfully with ATRA-ATO Therapy: A Case Study (BIRDEM Medical Journal, 2019)
Acute promyelocytic leukemia (APML) is the first malignant disease highly curable with targeted therapy directed at a unique molecular abnormality. The characteristic bleeding diathesis due to the combined effect of thrombocytopenia and disseminated intravascular coagulation is the most notorious manifestation of the disease, which historically has accepted for high mortality rate during induction. Acute promyelocytic leukemia is one of the few hematologic diseases that can be diagnosed with certainty by morphological examination of blood film and bone marrow aspirate by the practicing hematologist. Such step facilitates early institution of all-trans retinoic acid (ATRA) before molecular confirmation of the diagnosis. Therefore, ATRA therapy as well as aggressive blood product support is critical to reduce early mortality. Early diagnosis and prompt institution of appropriate therapy is essential as APML is a medical emergency and without rapid management patient may succumb due to bleeding diathesis. Also the prognosis of APML is much better than other subtypes of acute myeloid leukemia. ATRA plus anthracycline based chemotherapy for induction and consolidation followed by maintenance ATRA with low dose chemotherapy is currently the standard of care. However the combination of ATRA and arsenic trioxide (ATO), with minimal chemotherapy to control leukocytosis, is very effective therapy for newly diagnosed APML patients. The combination may replace conventional approaches to most, if not all, patients in the very near future. Here we report a case of APML of female who got admitted with fever, cough and pupuric rash throughout the whole body.Birdem Med J 2019; 9(1): 85-88